A sulfated galactan from the mucilaginous sheath of the red filamentous alga Chroodactylon ornatum (Stylonematophyceae, Rhodophyta) - Cabrera, Juan Manuel (2014)
The pseudofilamentous red alga Chroodactylon ornatum was grown in f/2 culture medium with the addition of 10, 34, and 100 μM (nominal concentration) cupric sulfate. The bioassays were terminated at two selected end points (days 4 and 12). Growth inhibition, changes in pigment composition, and oxidative stress indicators such as phenolic compounds and lipid peroxidation (dosed as thiobarbituric reactive substances) were observed in cultures with 34 and 100-μM cupric sulfate. Quinacrine (Atebrin) and chlorotetracycline fluorochromes showed abundant vacuoles of acidic content, related with mucilage secretion. Structural analyses by methylation, desulfation-methylation, alkaline treatment, and NMR spectroscopy revealed that the mucilaginous sheath of C. ornatum contains a sulfated galactan with a backbone of alternating 3-linked β-d-galactopyranose and 4-linked α-l-galactopyranose moieties, i.e., an agaran. The absence of 3,6-anhydrogalactose and of its precursor unit (α-galactose 6-sulfate) were confirmed. The highly sulfated polysaccharide contained these ester groups on the C-2 and C-4 hydroxyl groups of the 3-linked unit and on C-3 of the 4-linked units. The large proportion of sulfate esterification in this polysaccharide can be related to the extracellular biosorption of copper divalent cation (2.5 ± 0.4 mg per gram of dry weight) and to copper tolerance in bioassays.